Osimertinib in Japanese patients with EGFR T790M mutation‐positive advanced non‐small‐cell lung cancer: AURA3 trial - Akamatsu, Hiroaki; Katakami, Nobuyuki; Okamoto, Isamu; Kato, Terufumi; Kim, Young Hak; Imamura, Fumio; Shinkai, Masaharu; Hodge, Rachel A.; Uchida, Hirohiko; Hida, Toyoaki (Cancer science, 2018)
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are the first‐line treatment for patients with EGFR mutant non‐small‐cell lung cancer (NSCLC). However, most patients become resistant to these drugs, so their disease progresses. Osimertinib, a third‐generation EGFR‐TKI that can inhibit the kinase even when the common resistance‐conferring Thr790Met (T790M) mutation is present, is a promising therapeutic option for patients whose disease has progressed after first‐line EGFR‐TKI treatment. AURA3 was a randomized (2:1), open‐label, phase III study comparing the efficacy of osimertinib (80 mg/d) with platinum‐based therapy plus pemetrexed (500 mg/m2) in 419 patients with advanced NSCLC with the EGFR T790M mutation in whom disease had progressed after first‐line EGFR‐TKI treatment. This subanalysis evaluated the safety and efficacy of osimertinib specifically in 63 Japanese patients enrolled in AURA3. The primary end‐point was progression‐free survival (PFS) based on investigator assessment. Improvement in PFS was clinically meaningful in the osimertinib group (n = 41) vs the platinum‐pemetrexed group (n = 22; hazard ratio 0.27; 95% confidence interval, 0.13‐0.56). The median PFS was 12.5 and 4.3 months in the osimertinib and platinum‐pemetrexed groups, respectively. Grade ≥3 adverse events determined to be related to treatment occurred in 5 patients (12.2%) treated with osimertinib and 12 patients (54.5%) treated with platinum‐pemetrexed. The safety and efficacy results in this subanalysis are consistent with the results of the overall AURA3 study, and support the use of osimertinib in Japanese patients with EGFR T790M mutation‐positive NSCLC whose disease has progressed following first‐line EGFR‐TKI treatment. (ClinicalTrials.gov trial registration no. NCT02151981.) We examined the safety and efficacy results of a subgroup analysis of 63 Japanese patients enrolled in the AURA3 study, a randomized (2:1), open‐label phase 3 study comparing the efficacy of osimertinib (80 mg/d) with platinum‐based therapy plus pemetrexed (500 mg/m2) in 419 patients with advanced NSCLC with the EGFR T790M mutation whose disease had progressed after first‐line EGFR‐TKI treatment. In the Japanese subgroup, the hazard ratio was 0.27 (95% CI 0.13‐0.56), and the median progression‐free survival (primary endpoint) was 12.5 months in patients treated with osimertinib and 4.3 months in patients treated with platinum‐pemetrexed, which was clinically meaningful. The efficacy and safety findings in this subgroup of Japanese patients were consistent with those observed in the overall study population and suggested that osimertinib is effective as a standard regimen in Japanese NSCLC patients carrying the EGFR T790M mutation with disease progression after EGFR‐TKI therapy.